Analysis of Factors Related to The Incidence of Methicillin-Resistant Staphylococcus Aureus (MRSA) At Makassar City Hospital - Syam, Basri; Ismail, Mirna; Syam, Yuliana; Muslimin, Muslimin (Indonesian Contemporary Nursing Journal (ICON Journal), 2025)
Introduction: Nosocomial infections, including those caused by Methicillin-Resistant Staphylococcus aureus (MRSA), pose a significant challenge for the global health system. MRSA, a resistant bacterium that increases morbidity and mortality, is often found in healthcare facilities and is associated with inappropriate antibiotic use and suboptimal patient management practices. Methods: This research employs an analytical observational design with a cross-sectional approach. The sample consists of 70 inpatient medical records that meet the inclusion criteria, with data collected from positive MRSA microbiological cultures. Analysis was conducted using SPSS. Results: The results indicate a significant relationship between the type of laboratory examination (p=0.049), use of medical therapeutic devices (p=0.023), type of antibiotics (p=0.015), and duration of treatment (p=0.033) with MRSA incidence. Patients in the ICU and PICU had a higher prevalence, as did those receiving antibiotic treatment such as penicillin (p=0.015). A treatment duration of more than 7 days also increased the risk of MRSA infection (p=0.033). Additionally, devices such as catheters showed a significant association with infection (p=0.023). Conclusion: This study highlights the importance of strict infection surveillance and control in high-risk care units, appropriate antibiotic use, and monitoring of medical therapeutic devices. The findings can serve as a foundation for more effective infection prevention policies to minimize the risks and impacts of MRSA in healthcare facilities.